2011
DOI: 10.1371/journal.pgen.1002356
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 Governs Differentiation Stage-Specific Gene Expression in Growth Plate Chondrocytes via Direct Concomitant Transactivation and Repression

Abstract: Cartilage and endochondral bone development require SOX9 activity to regulate chondrogenesis, chondrocyte proliferation, and transition to a non-mitotic hypertrophic state. The restricted and reciprocal expression of the collagen X gene, Col10a1, in hypertrophic chondrocytes and Sox9 in immature chondrocytes epitomise the precise spatiotemporal control of gene expression as chondrocytes progress through phases of differentiation, but how this is achieved is not clear. Here, we have identified a regulatory elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
169
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 68 publications
(101 reference statements)
9
169
2
1
Order By: Relevance
“…SOX9 plays a key role in the regulation of sex determination, intestinal differentiation, cartilage development and adult progenitor cell pool maintenance (Jakob and LovellBadge 2011). During endochondral bone formation, SOX9 expression is down-regulated in growth plate chondrocytes (Leung et al 2011). The exact role of SOX9 in carcinogenesis and cancer progression is controversial because both oncogenic and tumor-suppressing functions of SOX9 have been described (Passeron et al 2009;Cai et al 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…SOX9 plays a key role in the regulation of sex determination, intestinal differentiation, cartilage development and adult progenitor cell pool maintenance (Jakob and LovellBadge 2011). During endochondral bone formation, SOX9 expression is down-regulated in growth plate chondrocytes (Leung et al 2011). The exact role of SOX9 in carcinogenesis and cancer progression is controversial because both oncogenic and tumor-suppressing functions of SOX9 have been described (Passeron et al 2009;Cai et al 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…This high cell compatibility of the HA-Mg 2+ -Na-polyP matrix was also reflected by the degree of gene inducibility elicited by this paste in comparison the free HA or Na-polyP. The qRT-PCR studies revealed that the gene encoding the transcription factor SOX9, which regulates chondrocyte differentiation, proliferation and entry into hypertrophy in immature and proliferating chondrocytes (Leung et al, 2011), was only significantly upregulated after a 21 d incubation period in chondrocytes in comparison to the controls (without any component), to HA or to Na-polyP alone. Likewise, the paste strongly enhanced the expression of collagen 3A1 (COL3A1), a cartilage matrix protein, marker for differentiation of chondrocytes both in vivo and in vitro (Aigner et al, 1997).…”
Section: +mentioning
confidence: 87%
“…Given that Sox9 is required for the expressions of Sox5 and Sox6 (3) and Sox9 transcription is suggested to be controlled by Sox9 itself (39), the initial events in this context may be an inhibition of the recruitment of Sox9 into its own regulatory regions by Gli1. However, a recent paper showed that there were conserved Gli-binding sites near the Sox motif in the Sox5 and Sox6 regions (40), which raised the possibility that an inhibitory action by Gli1 might occur in these regions. This study, however, does not address how Gli1 inhibits the recruitment of Sox9 onto DNA.…”
Section: Discussionmentioning
confidence: 99%